The Role of Macroeconomic Indicators and National Zakat Index in Advancing the Islamic Human Development Index (I-HDI): A Case Study of Districts and Cities in Banten Province - Pardiansyah, Elif; Ainun Najib, Mohamad (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This study examines the impact of macroeconomic indicators and the National Zakat Index (IZN) on the Islamic Human Development Index (I-HDI) at the district and city level in Banten Province. While the conventional Human Development Index (HDI) by the UNDP is widely accepted, its lack of alignment with Islamic principles makes it less suitable for assessing development in Muslim-majority areas. This research is original in integrating macroeconomic factors and zakat within an Islamic development framework. The primary purpose is to assess how economic growth, unemployment, poverty, and the National Zakat Index influence I-HDI. A quantitative approach using Ordinary Least Squares (OLS) and multiple regression analysis was applied. The findings reveal that economic growth has a positive and significant effect on I-HDI, highlighting its role in human development. Unemployment, although negatively correlated with I-HDI, does not have a significant impact, suggesting limited immediate effects. Poverty significantly impacts I-HDI, emphasizing the need for focused poverty alleviation efforts. While the National Zakat Index is positively correlated with I-HDI, its effect is not statistically significant, indicating that zakat optimization requires further attention. These results stress the importance of targeted policies to reduce poverty, stimulate economic growth, and enhance zakat distribution. Policymakers should work to improve the effectiveness of zakat and integrate it into broader economic and social strategies to improve I-HDI in the Islamic context. Penelitian ini menguji dampak indikator ekonomi makro dan Indeks Zakat Nasional (IZN) terhadap Islamic Human Development Index (I-HDI) di tingkat kabupaten dan kota di Provinsi Banten. Meskipun Indeks Pembangunan Manusia (IPM) konvensional oleh UNDP telah diterima secara luas, kurangnya keselarasan dengan prinsip-prinsip Islam membuatnya kurang cocok untuk menilai pembangunan di daerah mayoritas Muslim. Penelitian ini merupakan penelitian orisinil yang mengintegrasikan faktor ekonomi makro dan zakat dalam kerangka pembangunan Islam. Tujuan utamanya adalah untuk menilai bagaimana pertumbuhan ekonomi, pengangguran, kemiskinan, dan Indeks Zakat Nasional mempengaruhi I-HDI. Pendekatan kuantitatif menggunakan Ordinary Least Squares (OLS) dan analisis regresi berganda. Temuan menunjukkan bahwa pertumbuhan ekonomi memiliki pengaruh positif dan signifikan terhadap I-HDI, menyoroti perannya dalam pembangunan manusia. Pengangguran, meskipun berkorelasi negatif dengan I-HDI, tidak memiliki dampak yang signifikan, yang menunjukkan efek langsung yang terbatas. Kemiskinan berdampak signifikan terhadap I-HDI, menekankan perlunya upaya pengentasan kemiskinan yang terfokus. Meskipun Indeks Zakat Nasional berkorelasi positif dengan I-HDI, dampaknya tidak signifikan secara statistik, yang menunjukkan bahwa optimalisasi zakat memerlukan perhatian lebih lanjut. Hasil ini menekankan pentingnya kebijakan yang tepat sasaran untuk mengurangi kemiskinan, merangsang pertumbuhan ekonomi, dan meningkatkan distribusi zakat. Para pembuat kebijakan harus berupaya meningkatkan efektivitas zakat dan mengintegrasikannya ke dalam strategi ekonomi dan sosial yang lebih luas untuk meningkatkan I-HDI dalam konteks Islam.